Korean Red Ginseng Suppresses the Expression of Oxidative Stress Response and NLRP3 Inflammasome Genes in Aged C57BL/6 Mouse Ovaries - Sungwoo Chei; Hyun-Ji Oh; Hoon Jang; Kippeum Lee; Heegu Jin; Youngsok Choi; Boo-Yong Lee (Foods, 2020)
Female infertility and subfertility have been increasing in prevalence worldwide. One contributing factor is ovarian function, which is highly age-dependent. Korean red ginseng is widely used as an herbal medicine and has many beneficial properties. We aimed to determine the effect of the Korean red ginseng saponin fraction (KRGSF) on ovarian function in female C57BL/6 mice. Ovaries were isolated from 6- and 12-month-old female mice and treated with KRGSF, and then RNA was extracted and microarray analysis was performed. The expression of key genes was subsequently verified using quantitative RT-PCR. Aging markedly increased the expression of genes encoding oxidative stress factors and NLRP3 inflammasome components, but the expression of these genes was significantly reduced by KRGSF treatment. Thus, the reduction in ovarian health with age is associated with greater oxidative stress response and inflammation, but KRGSF treatment may limit these age-related changes.